O uso de poli(cloreto de vinila) quimicamente modificado para a adsorção de corantes básicos - Ali, Helena Maria de Almeida Mattos Martins dos Santos (2017)
Chemical modification of hydrophobic polymer matrices is an alternative approach of changing their surface properties. The introduction of sulfonic groups into the polymer modify the surface chemical properties, such as adhesion, wettability, catalytic capacity and adsorption capacity. This work describes the production and application of chemically modified polyvinyl chloride as an adsorbent for dye removal. The proposed modification through dehydrochlorination and sulfonation led to the production of a mesoporous material (PVDCS), it’s showing with average pore diameter of 5.76 nm and a high surface area (295,57 m2 g-1), compared to the source material (0.27 m2g-1). The functional changes confirmed by presence of the peak in 1159 cm-1, related to the group O=S=O. Elemental analysis showed a C/S molar ratio equal to 31, and with an atomic distribution, to the S atom of one to every 15 monomer units. The modified material (PVCDS) had striking characteristics, with CTI 1.03 mmol g-1, confirming the presence and availability of the sulfonic groups. By SEM images was verified that, with the chemical modifications, a material was formed with possible lamellar regions, apparently represented by scales and possible porous structures, justifying the increase of the surface area found. The results of XRX show an increase of the amorphous of the material with the chemical modifications. Studies related to adsorption kinetics of PVCDS resin with Lauth’s Violet dye show an experimental adsorption capacity of 11.96 mg g-1. The kinetic model that best fit the studied system, showed a better determination coefficient of 0.999936 and a greater proximity of the theoretical adsorption capacity 11.74 mg g-1, the experimental one, was that of pseudo-second order, demonstrating that the mechanism of adsorption possibly occurs by chemosorption. The studies equilibrium state model showed that the system presents a possible homogeneous structure for the active sites. Among the models, SIPS and Langmuir were the best fit to the studied system and presented the best determination coefficients with a high maximum adsorption capacity of 370 mg g-1. The modification promoted the formation of specific functional groups and surface characteristics favorable to the adsorption of the dye by the polymer.